PROBLEMS OF CORPORATE MANAGEMENT AND CONTROL IN JOINT-STOCK COMPANIES WITH STATE PARTICIPATION - A. Yakovlev (Вестник университета, 2018)
The problem areas in the sphere of corporate management of joint-stock com-panies with state participation are considered (the stocks belong to the Russian Federa-tion and subjects of the Federation). Due to the more complicated management and con-trol system in state joint-stock companies in comparison with private companies, they are characterized by a much larger number of problems. It is concluded that despite the dif-culties in management, it can not be argued that the public sector is initially less eec-tive. How exactly is the situation in reality is described in this study.